El imperio de la discrecionalidad judicial - Echeverry Restrepo, Carlos Andrés (2023)
This article aims to show some of the arguments that have fueled the debate over “judicial discretion,” an issue th at has become most evident in the changing value of so-called auxiliary cr iteria of judicial interpretation, like judicial opinions and legal doctrine, which in this case derive from constitutional case law. Such a change in appraisal (going from auxiliary to principal criteria, on equal footing with statutes), has produced a whirlwind of criticism and support, enhanced by so me informative flippancy from mass media, which is still far from abating. Nevertheless, such doctrinal disputes help strengthen the theoretical corpus of Colombian law, still in evolution.